Остеосинтез у разі переломів шийки та вертлюгової зони стегнової кістки в дітей - Popsuishapka, Olexii; Dovhan, Serhii; Khomyak, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Proximal femur fractures are uncommon injuries in children, accounting for less than 1 % of all fractures per year, but usually result in hospitalization and are at risk of complications. We have designed a device for bone fragments fixation in the case of proximal femur fractures and the method of its application in adults. The device consists of rods that are screwed into the cap of the head, the diaphyseal part and the module, which is located in the subtrochanter area. The rods can be connected to the module at any angle in the frontal plane. The device provides a certain stage of installation of the elements, which allows you to effectively place it with minimal bone destruction. Objective. Share your own experience in the treatment of femoral neck and proximal femur fractures in children. Material. The experience of treatment of 28 children with femoral neck fracture or proximal femur fractures for the period 2005–2020 is presented, 11 of them were treated conservatively with the skeletal traction. Osteosynthesis by the author’s device was performed in 17 patients: 15 closed reduction, 2 in case of intertrochanteric fracture, — open reduction. The method of osteosynthesis and postoperative management of patients is described in detail. Results. In children who were treated conservatively, the fracture consolidation was achieved within 5–7 months, in one of them — in the position of varus deformity. In contrast to conservative treatment, children began to walk with crutches after a few days after surgery, with partial weight-bearing on injured limb. The device was removed in 16 patients after 5–8 months, and complete fracture consolidation of the fragments in their anatomical position was noted. There were no pathological tissue reactions to the metal device. Conclusions. The proposed device and method of closed osteosynthesis with its usage in the case of proximal femur and femoral neck fractures in children can be recommended in the practice of pediatric traumatology.